The reality, provisions and conditions of Aqilah - Muhammad Husni, Ahmad; Omar, Anwar Fakhri (Medwell Journal, 2014)
There have been many accidents which result in deaths due to motor accidents which is the majority or hunting or Jihad or other things that result in crime. We find that a lot of people are unaware of the provisions of manslaughter and that the blood money is paid by Aqilah and this is something unknown to some people. Thus, I explained the reality of Aqilah and the important issues that may be hidden to many people. And here lies the importance of this research, and also to know its provisions and conditions through the extrapolation of the views of the four Schools, and to analyse, discuss and clarify the points of agreement and disagreement between them. Moreover, it looked into the views of contemporary scholars to choose the provisions that fit the development of the current era. Through the study, we reached to some important results, most important of which if the offender has no Aqilah, or he has but the Aqilah is unable to pay the blood money (diyyah) for him, it should be paid from the Baitulmal or its representative.